2009
DOI: 10.1590/s1415-790x2009000300015
|View full text |Cite
|
Sign up to set email alerts
|

Estado nutricional e níveis de hemoglobina em crianças Aruak e Karibe: povos indígenas do Alto Xingu, Brasil Central, 2001-2002

Abstract: Objective: To evaluate the nutritional status of indigenous children of the Aruak and Karibe linguistic families from the Upper Xingu, Central Brazil, and study the relationship between hemoglobin levels and children's gender, age and nutritional status. In total, 470 children under age ten were studied in 2001/2002. Methods: For children under five years old, the diagnosis of undernutrition was based on the heightfor-age and weight-for-age indices, with a cutoff value of two standard deviations below the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
4
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 12 publications
5
4
0
6
Order By: Relevance
“…However, although reports of malnutrition, in general, characterise children's anthropometric profiles among indigenous peoples, the increase in children with obesity in this population merits particular attention. Evaluating the nutritional status of indigenous children from Alto Xingu, and in a study of the nutritional profile of indigenous Kaingáng children, Mondini et al 34 and Kuhl et al 35 , respectively, also found a marked percentage of overweight, similar to that observed in this study. The authors also noted that these findings are not isolated cases in the indigenous context and note that recent studies have identified cases of overweight amongst children from different indigenous groups.…”
Section: Discussionsupporting
confidence: 87%
“…However, although reports of malnutrition, in general, characterise children's anthropometric profiles among indigenous peoples, the increase in children with obesity in this population merits particular attention. Evaluating the nutritional status of indigenous children from Alto Xingu, and in a study of the nutritional profile of indigenous Kaingáng children, Mondini et al 34 and Kuhl et al 35 , respectively, also found a marked percentage of overweight, similar to that observed in this study. The authors also noted that these findings are not isolated cases in the indigenous context and note that recent studies have identified cases of overweight amongst children from different indigenous groups.…”
Section: Discussionsupporting
confidence: 87%
“…This scenario is in agreement with that observed in the most recent surveys [10][11][12][21][22][23][24] and with nationwide studies [25][26][27][28][29][30][31] as well as with those undertaken in other Latin American countries [3][4][5][6][7] .…”
Section: Discussionsupporting
confidence: 92%
“…Concerning the indigenous population, Castro et al 30 found a prevalence of 15.5% among children of less than 10 years of age of the Kaingáng tribe of the south of Brazil. For the same age group, Mondini et al 31 observed prevalences of 28.2% and 15.06% in children of the Aruak and Karibe tribes, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…Por exemplo, é somente dentre os estudos realizados em comunidades indígenas brasileiras que se encontram referências a frequências de desnutrição crônica superior a 50% em crianças menores de cinco anos, e da ordem de 80% de anemia nesta mesma faixa etária 17,18,19 . Nas comunidades indígenas onde a tuberculose é endêmica, mais de 60% das notificações têm sido reportadas em crianças 20,21 .…”
Section: Saúde E Nutrição Da Criança E Da Mulher Indígenaunclassified